Relationship between transactional and transformational styles and turnover in sport organizations - Ghezelseflou, Hamid Reza; Ashouri, Taghi (International Journal of Applied Behavioral Sciences, 2017)
Introduction: The purpose of this research was relationship between effective style’s management with employee’s efficiency and turnover in sport organization.Methods: Statistical population consist of all sport manager and sports staff of Golestan physical education that n= 37 top sport manager and n= 137 performational and middle manager selected as sample size. The multi-factor leadership questionnaire (MLQ, Bass & Avolio, 1996), Amabil (1996) organization creativity questionnaire and Felts (1998) self-efficiency questionnaire were used. To data analysis the MANOVA test, multi-regression analysis and Pearson coefficients in significance level of (P≤0.05) were used.Results: The results indicated that transformational style management (F=9.74, β=0.316) in comparison with transactional style management (F=5.019, β=0.109) and laissez-faire management (F=4.263, β=0.002) is the strongest factor in determination of employee creativity. Also there were significant relationship between transformational style management with staff efficiency(r= 0.23, p≤ 0.05) and turnover in employees(r = - 0.11, p≤ 0.05) .But there weren’t significant and meaningful relationship between management styles with turnover. In other organizations that were use laissez-faire management, there were significant relationship between laissez-faire management style with turnover (r= 0.14, p≤ 0.05).Conclusion: Based on findings of research, suggests that employee turnover may be substantially reduced if sport manager exhibit behaviors which reflect employees’ expectations of quality management.